DELIVERY OF A DICEPHALUS-THORACO-STERNOPAGUS TETRABRACHIUS DICAUDATUS MONSTER IN BUFFALO - SUNDER, SHYAM; KUMAR, SANDEEP; SINGH, GYAN; DUTT, RAVI; PANDEY, A K (The Indian Journal of Animal Reproduction, 2011)
A rare case of dystocia due to dicephalic-thoracopagus tetrabrachius dicaudatus monster was relieved by partial fetotomy.